2022
DOI: 10.2147/dmso.s351155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultra-Long-Acting Insulin Compared to Long-Acting Insulin on Diabetic Ketoacidosis Incidence in Type 1 Diabetes Mellitus Patients

Abstract: Purpose This research was intended to explore the effects of new-generation basal insulin (degludec U100 And glargine U300) versus long-acting basal insulin (glargine U100, detemir) on the incidence of diabetic ketoacidosis episodes and diabetes treatment measures. Patients and methods This is a cross-sectional, retrospective medical record analysis. The study population included adults with type 1 diabetes mellitus (DM) who were on the hospital records in 2020. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, data from Saudi Arabia on switching patients from long-acting insulin are scarce. A retrospective study by Alsofiani et al reported the incidence of diabetic ketoacidosis (DKA) in type 1 DM patients using insulin glargine (U300) compared to insulin degludec (U100) after six months [ 20 ]. Although the focus was to evaluate the incidence of DKA, for which there was a difference between the two groups, they reported no change in HgbA1c between the two therapies (9.9 vs 9.8, respectively; P>0.05), which suggests that there were no clinical benefits between the two agents in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data from Saudi Arabia on switching patients from long-acting insulin are scarce. A retrospective study by Alsofiani et al reported the incidence of diabetic ketoacidosis (DKA) in type 1 DM patients using insulin glargine (U300) compared to insulin degludec (U100) after six months [ 20 ]. Although the focus was to evaluate the incidence of DKA, for which there was a difference between the two groups, they reported no change in HgbA1c between the two therapies (9.9 vs 9.8, respectively; P>0.05), which suggests that there were no clinical benefits between the two agents in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Although the focus was to evaluate the incidence of DKA, for which there was a difference between the two groups, they reported no change in HgbA1c between the two therapies (9.9 vs 9.8, respectively; P>0.05), which suggests that there were no clinical benefits between the two agents in this population. However, the same study reported that insulin glargine (U300) users had higher insulin dose requirements when compared to insulin degludec (U100) users [ 20 ]. A Japanese study revealed that switching to insulin degludec resulted in better glycemic control in 16 weeks with lower insulin dosing requirements [ 21 ].…”
Section: Introductionmentioning
confidence: 99%